Penerapan Strategi Pembelajaran Think Talk Write (TTW) dalam Meningkatan Keterampilan Menulis Teks Eksposisi Analitis pada Peserta Didik - Sari Siregar, Elvilida (Journal of Education Action Research, 2018)
This study aims at finding out and describing (1) the implementation of TTW learning strategy in improving students’ writing competency in analytic exposition text in class XI P2 SMK Negeri 2 Singaraja in academic year 2017/2018, (2) the appropriate learning steps for TTM strategy implementation in writing analytic exposition text of students in class XI P2 SMK Negeri 2 Singaraja in academic year of 2017/2018, (3) students’ response in class XI P2 SMK Negeri2 Singaraja while learning analytic exposition text through the use of TTW strategy. It is a two-cycles study with the total students of 40 people in class XI P2 SMK Negeri 2 Singaraja. The data of students’ writing competency in analytic exposition text through the use of TTW strategy were collected through test at the end of the learning. Data of the learning procedures were collected through observation technique and data of students’ response towards its implementation were collected through observation and questionnaires. The result of the study showed that the implementation of TTW strategy could improve students’ writing competency in analytic exposition text. The improvement of students’ writing competency was about 35%, from 32.5% to 67.5%. The learning session was considered to be successful for around 80% of the students could gain the scores above the standard score. The students (92% of them) gave positive response while implementing TTW strategy in writing analytic exposition text